Central serotonin receptors and delayed gastric emptying in non-ulcer dyspepsia. Issue 6848 (1st August 1992) - Chua, A.; Keating, J.; Hamilton, D.; Keeling, P. W.; Dinan, T. G.
Abstract : OBJECTIVE–To determine whether central serotonin receptors are involved in the pathophysiology of non-ulcer dyspepsia. DESIGN–Between subjects study of solid phase gastric emptying and prolactin response to buspirone challenge. SUBJECTS–12 patients fulfilling criteria for non-ulcer dyspepsia and 12 age and sex matched controls. MAIN OUTCOME MEASURES–Solid phase gastric emptying measured by scintigraphic assessment of the movement of a standard meal labelled with technetium-99m and indium-111; responsiveness of central serotonin 1A receptors measured by the prolactin release following challenge with oral buspirone 60 mg. RESULTS–Solid phase gastric emptying was significantly delayed in the patients with non-ulcer dyspepsia (t 1/2 = 90.6 (SD 14.5) minutes in patients and 54.6 (10.7) minutes in controls; 95% confidence interval 24.7 to 46.7 minutes, p < 0.001). Prolactin release was significantly greater in patients compared with controls (1272.7 (1039.9) mU/l v 292.9 (136.1) mU/l; 352.1 to 1607.5 mU/l, p < 0.01). Gastric emptying and prolactin release were significantly correlated (r = 0.59, p = 0.04) in the patients but not in the controls (r = 0.23). CONCLUSION–Central serotonin 1A receptors may have a role in the pathophysiology of non-ulcer dyspepsia of the dysmotility subtype.